Currently unavailable: until 02/02/2017

Degree: Mathematics (Bachelors) - Cardiff University

MyTutor guarantee

|  1 completed tutorial

I am currently in my second year of studying Maths at Cardiff Universty. I love my subject and as a tutor I hope to inspire and instill that love within my students. I'm laid back, friendly, and love to teach. I have been doing Taekwondo for more than 12 years and teaching younger students since the age of 15. This has taught me to be patient and kind, and I take great pride when helping someone overcome any issues. I can't wait to get started with you!

#### Subjects offered

SubjectQualificationPrices
Maths A Level £20 /hr
Maths GCSE £18 /hr

#### Qualifications

MathematicsA-levelA2A
Further MathematicsA-levelA2A
Art and DesignA-levelA2B
 CRB/DBS Standard No CRB/DBS Enhanced No

#### General Availability

Currently unavailable: until

02/02/2017

Weeks availability
MonTueWedThuFriSatSun
Weeks availability
Before 12pm12pm - 5pmAfter 5pm
MONDAY
TUESDAY
WEDNESDAY
THURSDAY
FRIDAY
SATURDAY
SUNDAY

Please get in touch for more detailed availability

#### Ratings and reviews

0from 1 customer review

Najma (Parent) September 27 2016

coudlnt hear her had to cancel
See all reviews

### Find the equation of the tangent to the curve y = 2 ln(2e - x) at the point on the curve where x = e.

The first step is to find the y coordinate at the point on the curve where x = e. To do this we subsitute x = e into the equation of the curve, so y = 2ln(2e - x) becomes y = 2ln(2e - e). Simplifying this, we get y = 2ln(e). Using our knowledge of the natural logarithm, ln(e) = 1, so therefore...

The first step is to find the y coordinate at the point on the curve where x = e. To do this we subsitute x = e into the equation of the curve, so y = 2ln(2e - x) becomes y = 2ln(2e - e). Simplifying this, we get y = 2ln(e). Using our knowledge of the natural logarithm, ln(e) = 1, so therefore y = 2.

Next, we find the gradient of the curve at the point x = e. We do this by differentiating the equation, and then subsituting the value for x in. Note that we have to use the chain rule.

dy/dx =  -2/(2e - x) = -2/(2e - e) = -2/e.

Using all the information we've found, we can now produce the equation of the tangent line using the equation of a line formula, y - y= m(x - x0), where m is the gradient.

y - 2 = -2/e (x - e). Rearranging this, we get y = 4 - 2x/e as the equation of the tangent line.

see more

1 year ago

954 views
Send a message

All contact details will be kept confidential.

To give you a few options, we can ask three similar tutors to get in touch. More info.

Still comparing tutors?

How do we connect with a tutor?

Where are they based?

How much does tuition cost?

How do tutorials work?

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this.